Semantic Analogy of Quran Text Content Found in Ornamental Figures in Islamic Architecture: وسام كامل عبد الامير (Al-Academy, 2016)
This study aims at creating an analogy between Quran text Contents as meanings that have representations as visional shapes within ornamental figures in Islamic architecture. The theoretical framework of the study deals with the concept of semantics and its parts, artistic contents of Quran texts, and ornamental figures in Islamic architecture. The study procedures included a population of (69) figures, (5) of them were chosen deliberately for analysis in accordance with a form that had been presented to a number of experts to ensure its validity. The study reached a number of conclusions, the most significant among them are: adopting natural denotation of direct reference in order to link the ornamental figure to the source it was taken from via depending on analogy of the realistic (source/blueprint) and the ornamental adapted (copy) as in animal and plant figures, which is pinpointed either (iconically) through the ornamental figure imitation of reality, and (indicatively) through linking cause to effect (consequence) to identify a hidden fact, and (symbolically) without relying on causality; analogy between Quran text content (meaning = an idea) and ornamental figures in Islamic architecture (the word) includes content of oneness and perfection and its representation in ornamental figures and content of order and abstractness as a view that goes beyond the obvious limits of figure to reach what lies behind that, and the content of repetition that involves repeating an event in terms of time and place in a cyclic way that imitates ornamentally prevalence, completion, and reproduction of new figures through reordering components; and the meaning underlining ornamental figures seeks to reflect an aesthetic picture of reality with a subjective vision of ornamental figures and an objective vision of the components employed in ornamenting Islamic architecture through the styles of (capturing and envisioning) which are divided into concrete: through direct capturing with a slight modification for aesthetic reasons as in trees and instinctive: through mental discerning and realization of figures order and the abstract connections within this order by (envisioning) a figure that turns what is mentally realized to an entity that has actual existence